Dos textos renacentistas sobre las humanidades, traducción, introducción y notas de joeaquin barceló - Barceló, Joaquín (Revista Chilena de Humanidades, 2015)
The translation of two Latín texts of Leonardo Bruni - to our notice the first into a modern tongue - made with an introduction and comments by Professor Joaquín Barceló, permits us to become acquainted with the first attempt to define the conte nts of humanistic studies which in a Large measure has relevance to our own days and which, consequently, establishes paradigms for fruitful comparison with later criteria.